Cross-Talk between Obesity and Diabetes: Introducing Polyphenols as an Effective Phytomedicine to Combat the Dual Sword Diabesity - Shah, Muhammad A.; Haris, Muhammad; Faheem, Hafiza Ishmal; Hamid, Ayesha; Yousaf, Rimsha; Rasul, Azhar; Shah, Ghulam Mujtaba; Khalil, Atif A. K.; Wahab, Abdul; Khan, Haroon; Alhasani, Reem Hasaballah; Althobaiti, Norah A. (Current Pharmaceutical Design, 2022)
Obesity-associated diabetes mellitus, a chronic metabolic affliction accounting for 90% of all diabetic patients, has been affecting humanity extremely badly and escalating the risk of developing other serious disorders. It is observed that 0.4 billion people globally have diabetes, whose major cause is obesity. Currently, innumerable synthetic drugs like alogliptin and rosiglitazone are being used to get through diabetes, but they have certain complications, restrictions with severe side effects, and toxicity issues. Recently, the frequency of plant-derived phytochemicals as advantageous substitutes against diabesity is increasing progressively due to their unparalleled benefit of producing less side effects and toxicity. Of these phytochemicals, dietary polyphenols have been accepted as potent agents against the dual sword “diabesity”. These polyphenols target certain genes and molecular pathways through dual mechanisms such as adiponectin upregulation, cannabinoid receptor antagonism, free fatty acid oxidation, ghrelin antagonism, glucocorticoid inhibition, sodium-glucose cotransporter inhibition, oxidative stress and inflammation inhibition etc. which sequentially help to combat both diabetes and obesity. In this review, we have summarized the most beneficial natural polyphenols along with their complex molecular pathways during diabesity.
Keywords: diabetes